Cellular mechanisms underlying cardiac engraftment of stem cells. (2nd September 2017) - Kanda, Pushpinder; Davis, Darryl R
ABSTRACT: Introduction : Over the past decade, it has become clear that long-term engraftment of any ex vivo expanded cell product transplanted into injured myocardium is modest and all therapeutic regeneration is mediated by stimulation of endogenous repair rather than differentiation of transplanted cells into working myocardium. Given that increasing the retention of transplanted cells boosts myocardial function, focus on the fundamental mechanisms limiting retention and survival of transplanted cells may enable strategies to help to restore normal cardiac function. Areas covered : This review outlines the challenges confronting cardiac engraftment of ex vivo expanded cells and explores means of enhancing cell-mediated repair of injured myocardium. Expert opinion : Stem cell therapy has already come a long way in terms of regenerating damaged hearts though the poor retention of transplanted cells limits the full potential of truly cardiotrophic cell products. Multifaceted strategies directed towards fundamental mechanisms limiting the long-term survival of transplanted cells will be needed to enhance transplanted cell retention and cell-mediated repair of damaged myocardium for cardiac cell therapy to reach its full potential.